2018
DOI: 10.1088/1674-1056/27/5/055202
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic plume morphologies of atmospheric Ar and He plasma jets excited by a pulsed microwave hairpin resonator

Abstract: Different discharge morphologies in atmospheric Ar and He plasmas are excited by using a pulsed microwave hairpin resonator. Ar plasmas form an arched plasma plume at the opened end of the hairpin, whereas He plumes generate only a contracted plasmas in between both tips of metal electrodes. Despite this different point, their discharge processes have three similar characteristics: (i) the ionization occurs at the main electrode firstly and then develops to the slave electrode, (ii) during the shrinking stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
0
9
0
3
Order By: Relevance
“…It has been reported that the atmospheric pressure microwave He plasma was confined around the central electrode and showed a point discharge form, so the plasma jet could not eject from the nozzle. [23,24] In this study, the atmospheric pressure microwave He plasma jet and He/N 2 plasma jet are produced by adjusting the working gas intake mode and the working gas composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the atmospheric pressure microwave He plasma was confined around the central electrode and showed a point discharge form, so the plasma jet could not eject from the nozzle. [23,24] In this study, the atmospheric pressure microwave He plasma jet and He/N 2 plasma jet are produced by adjusting the working gas intake mode and the working gas composition.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [23] indicated that, when the increase of operating frequency was from 0.9 to 2.45 GHz, the Ar plasma showed contracted and filamentary plasma plumes while only contracted plasma was found at the central electrode for He plasma. Chen et al [24] also found different morphologies of plasma jets when a pulsed microwave hairpin resonator was used to excite Ar and He gases. An arched Ar plasma jet was found at the hairpin opened end while a constricted He plasma jet formed between the electrode tips.…”
Section: Introductionmentioning
confidence: 99%
“…本文构建了三种不同等 离子体位型的仿真模型, 分别为拱形等离子体、月牙形等离子体和类椭圆形等离子体. 仿真模型 由'U'形金属丝发卡、谐振腔、石英管、SMA 端口等组成; 设置输入 1 W 微波功率, 建立模型 的相关细节可以在之前的文章中看到 [18,24] .…”
Section: 电磁模型与仿真unclassified
“…J K Lee 课题组 [8] 发现微波放电射流随气体 成分和微波频率的改变表现出不同的形态. 陈兆权等人 [13,14,[21][22][23] 性相反 [12,18,24] . 将发卡尖端削尖至 0.05 mm, 以便更容易触发放电.…”
unclassified
“…此外, 在材料表面等离子体改性和镀膜应用领域, 大气 压低功率微波等离子体射流的参数优越且不需要真空 系统, 竞争优势明显 [123][124][125][126][127][128][129] , 等等.…”
Section: 了微波放电点燃丙烷的研究 国内 大连理工大学联合unclassified